The Impact of Puppet Show Media on Grade 3 Students' Listening Skills at SDN 1 Syamtalira Bayu - Firdha Dwi Apriani; Maya Safitri; Jumat Barus (PGMI IAIN Lhokseumawe, 2023)
The low creativity of teachers in determining learning media makes students experience difficulties in listening. One of the things that underlies the achievement of learning is the availability of media in the teaching and learning process. Therefore, the researcher formulated this study with the title